Trends in immediate breast reconstruction across insurance groups after enactment of breast cancer legislation. Issue 13 (12th April 2013) - Yang, Rachel L.; Newman, Andrew S.; Lin, Ines C.; Reinke, Caroline E.; Karakousis, Giorgos C.; Czerniecki, Brian J.; Wu, Liza C.; Kelz, Rachel R.
Abstract : BACKGROUND: To improve access to breast reconstruction for mastectomy patients, the United States enacted the Women's Health and Cancer Rights Act in January of 1999. The objective of the current study was to evaluate the impact of this legislation on patients with different insurance plans. METHODS: Women aged ≥18 years who underwent mastectomy for cancer were identified in the Nationwide Inpatient Sample database (2000‐2009) and were classified according to their immediate breast reconstruction (IBR) status. Trends in rates of IBR were described for each insurance category. Multivariable logistic regression analysis with adjustment for age, race, estimated household income, and Elixhauser comorbidity index was performed to evaluate the relation between insurance status and IBR. RESULTS: In total, 168, 236 patients were identified who underwent a mastectomy during the study interval. Across the 10‐year study period, rates of IBR increased 4.2‐fold in Medicaid patients, 2.9‐fold in Medicare patients, 2.6‐fold in privately insured patients, and 2.1‐fold in self‐pay patients ( P < .01). However, after adjustment for confounders, women without private insurance were less likely to undergo IBR compared with women who had private insurance (Medicaid: odds ratio [OR], 0.34; 95% confidence interval [CI], 0.32‐0.37; Medicare: OR, 0.53; 95% CI, 0.49‐0.58; self‐pay: OR, 0.43; 95% CI, 0.37‐0.50; other types of nonprivate insurance: OR, 0.64, 95% CI, 0.56‐0.73). CONCLUSIONS: After the enactment of policy designed to improve access to IBR, Medicaid and Medicare patients experienced the greatest relative increase in rates of IBR. Although policy changes had the most impact on traditionally underserved populations, disparities still exist. Future studies should endeavor to understand why such disparities have persisted. Cancer 2013;119:2462‐2468 . © 2013 American Cancer Society . Abstract : After the enactment of policies designed to improve access to breast reconstruction, overall rates of postmastectomy immediate breast reconstruction increased. Medicaid and Medicare patients saw the greatest relative rise in rates of immediate breast reconstruction, yet their likelihood of undergoing immediate breast reconstruction still remains low compared with privately insured patients.